2019
DOI: 10.1111/pai.13130
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life associated with maternal anxiety disorder in Russian children and adolescents with food allergy

Abstract: BackgroundFood allergy negatively impacts the quality of life (QoL) and has been associated with increased maternal anxiety. There is currently a lack of data assessing QoL of food‐allergic children and adolescents in Russia. We aimed to evaluate the performance of the Food Allergy Quality of Life Questionnaire (FAQLQ) measures in a Russian sample of children, adolescents, and mothers and to investigate association between child QoL and maternal general anxiety.MethodsFAQLQ and Food Allergy Independent Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
1
14
1
3
Order By: Relevance
“…Caregiver anxiety was significantly correlated with almost all proxy‐reported measures of child impact, partially supporting previous research finding maternal anxiety is significantly associated with child's proxy‐reported HRQL in FA 11,13 . However, while caregiver sex was also significantly associated with child's PA burden for almost all FAQLQ outcomes, our findings suggest that male caregivers report higher levels of burden experienced by their child than female, whereas previous research has found mothers reported greater burden for their child than fathers reported 9 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Caregiver anxiety was significantly correlated with almost all proxy‐reported measures of child impact, partially supporting previous research finding maternal anxiety is significantly associated with child's proxy‐reported HRQL in FA 11,13 . However, while caregiver sex was also significantly associated with child's PA burden for almost all FAQLQ outcomes, our findings suggest that male caregivers report higher levels of burden experienced by their child than female, whereas previous research has found mothers reported greater burden for their child than fathers reported 9 .…”
Section: Discussionsupporting
confidence: 82%
“…In line with recent findings, a child's sex was not associated with proxy-reported child burden, 12 with child's proxy-reported HRQL in FA. 11,13 However, while caregiver sex was also significantly associated with child's PA burden for almost all FAQLQ outcomes, our findings suggest that male caregivers report higher levels of burden experienced by their child than female, whereas previous research has found mothers reported greater burden for their child than fathers reported. 9 It is possible that this novel finding is due to previous studies lacking male caregivers in their sample; alternatively, this may reflect the increase in shared parenting and greater involvement of males in childcare.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous studies on food allergy have used a variety of anxiety and QoL tools 10 , 11 , 12 , 13 , 14 and used in diverse populations. 2 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…While factors associated with FAAA could be clearly identified, they also conclude that generic anxiety and QOL tools did not accurately categorize parents with self‐reported high FAAA. Parental anxiety has been reported earlier in PAI as an important factor impacting the QoL of families with children suffering from food allergies 17,18 .
…”
mentioning
confidence: 90%